Understanding of Gunung Tua Julu Village Community About Sharia Banking (Case Study in Gunung Tua Julu Village, Panyabungan District, Mandailing Natal Regency) - Dahliana, Riski (AMK : Abdi Masyarakat UIKA, 2024)
Riski Dahliana (Nim. 20150043), Understanding of Gunung Tua Julu Village Community About Islamic Banking (Case Study in Gunung Tua Julu Village, Panyaungan District, Mandailing Natal Regency). The purpose of this study was to find out about the understanding of the Gunung Tua Julu Village Community, Panyaungan District, about Islamic banking. This type of research is field research conducted in Gunung Tua Julu Village. The nature of this study is a qualitative descriptive method. There are two data sources in this study, namely primary and secondary data sources. Primary data sources are obtained directly from the community while secondary data sources are in the form of Gunung Tua Julu village documents and books. To obtain valid data, the researcher uses a data collection method, namely interviews. After the data is collected, the researcher analyzes the data using qualitative data analysis techniques using the inductive method. The results of field research show that the understanding of the Gunung Tua Julu Village Community about Islamic banking is still minimal. They only know about Islamic banks but do not understand Islamic banks in detail. Only a few people understand about Islamic banks, some even do not know about Islamic banks at all. Most people do not know about what products and services are available at Islamic banks. The lack of understanding from the community is due to the lack of information obtained from Islamic banks and media such as television, print media, and social media which causes the community not to know what Islamic banks are and what products are available at Islamic banks.